The effects of ESG management on process innovation: The case of cement industry - Chen, Shun-Hsing; Huang, Yu-Chung (goodwood publishing, 2024)
Purpose: In the past, companies placed significant emphasis on Earnings Per Share (EPS) financial performance, while Environment Social Governance (ESG) is now used to assess a company's comprehensive performance in the areas of environment, social responsibility, and corporate governance. Research Methodology: This study employs qualitative research through in-depth interviews and utilizes the SWOT analysis method. This study aims to conduct an in-depth investigation into Taiwan Asia Cement's future carbon management strategy, anticipating and positioning itself to turn the crisis into an opportunity, ultimately becoming a major winner in the era of climate change and a low-carbon economy. Results: The primary objectives are to understand the innovative process of promoting low-carbon cement manufacturing by Taiwan Asia Cement and to investigate consumers' willingness to use this cement. The study reveals that Asia Cement has established a low-carbon cement promotion team, actively collaborating with consumers to increase the adoption of low-carbon cement, resulting in a stable market growth rate. Limitations: The marketing strategies in this study are more useful for the cement industry only and are not applicable to competitive marketing strategies in other industries. Contribution: Additionally, interviews uncover that consumers using low-carbon cement are mainly located in eastern Taiwan. Many consumers in this region have not heard of or used low-carbon cement, indicating significant marketing opportunities. Novelty: In an environment where the world is emphasizing ESG, it is important to enhance the corporate image of the cement industry through process innovation to contribute to environmental issues.